Financial Statement Fraud Risk and Financial Distress of Family Business: Socio-Emotional Wealth (SEW) Perspective - Abdul Ghofar; Amran Rasli; Silvi Asna Prestianawati (Universitas Pendidikan Ganesha, 2024)
This study examines the risk of financial statement fraud in family businesses and explores financial distress as a moderating variable. The research sample consists of 306 businesses in Indonesia. The findings reveal that family businesses in Indonesia tend to avoid fraud to protect their family reputation, consistent with the Socio-Emotional Wealth (SEW) theory. However, financial distress is also found to mitigate the negative effects of family ownership on the risk of financial statement fraud. Furthermore, the results indicate no significant difference between the first and second-generation controllers in their attitudes towards the risk of financial statement fraud, aligning with the SEW theory. This research contributes to the accounting literature by providing insights into the unique dynamics of family businesses, particularly in the context of financial distress. It highlights the importance of considering both family ownership and financial conditions when assessing the risk of fraud. These findings are valuable for family business owners, policymakers, and practitioners, offering guidance on maintaining business value and implementing effective governance policies to prevent financial statement fraud.